NAJAH TADRIS AL-LUGHAH AL-‘ARABIYYAH BI AL-MUDKHALAT (AL-FI’AH AL-MUSTAHDAFAH) AL-JAYYIDAH - Niswatush Sholihah (Jurnal Alsinatuna, 2016)
Learning is basically an attempt to change or improve one's potential, prospective students (raw input) into a new individual (raw output) with a certain quality. Learning has three important elements, namely input, process and output. These three elements are closely interconnected. Indicators of learning success vary from one school to another school. By using qualitative method, this article aims to describe the success of Arabic language learning through selection process of new admissions to get quality student input because the quality of student input is one of the success factors of learning at school. Therefore, it is necessary for schools to held a selection of new admissions to get quality student input, so that the learning success will be easier to achieve.